What If We're Not Nongovernmental Organizations (NGOs) : The Opportunities Ahead for International Development NGOs - Glenzer, Kent (2012)
International development NGOs (IDNGOs) have both flourished and been objects of cogent critique over the past twenty years. The populations and budgets of IDNGOs continue to grow even as concerns about accountability, quality, and cost persist. Meanwhile, major inroads have been made on reducing poverty, driven not by official development assistance (ODA) but by market forces.